Enhancing Students’ Literacy with the Transformation of Local History and Culture Materials into Whiteboard Animation Based on the Bengkulu Provincial Museum Collection - Setiawan, Yudi; Wijanarko, Andang; Purwandari, Endina Putri; Dianita, Meisy; Lakshita, Stefanie Laksmi (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
Background: Effective pedagogy requires innovative media to enhance student literacy and contextual understanding, particularly in local history and culture. This community service project addresses the need for engaging teaching methods by utilizing whiteboard animation to transform collections from the Bengkulu Provincial Museum into accessible learning resources.Aims: This study aims to enhance student literacy in local history and culture and simultaneously strengthen teachers' digital media development competence through the implementation of whiteboard animation–based learning media.Method: The activity was conducted at SMP Negeri 02 Kota Bengkulu, employing three key stages: observation, socialization, and evaluation. The socialization included hands-on training for teachers on creating digital media (using Canva and SpeedPaint) and presenting the new historical content to students. The effectiveness of the learning intervention was quantitatively assessed using the Normalized Gain (N-Gain) method.Results: The intervention yielded significant positive outcomes. Teachers' professional competence in digital animation increased by 60 percentage points, and their satisfaction was 4.6/5. For students, the average literacy score increased by 31.7%, resulting in an N-Gain value of 0.53 (moderate effectiveness). Furthermore, student participation and satisfaction were very high (4.7/5).Conclusion: Whiteboard animation has proven to be an effective and engaging learning model that successfully enhances student literacy while simultaneously supporting the preservation of local history and cultural values in a manner relevant to the digital era.